Harnessing Artificial Intelligence: Transformative Technologies in Contemporary Higher Education - Doris Chasokela (Scientia Publica Media, 2025)
Artificial Intelligence has rapidly become a transformative force within the contemporary higher education landscape, altering how teaching methodologies, learning experiences, and administrative functions are structured and delivered. The advancement of AI technologies presents opportunities and challenges that institutions must carefully navigate. This study explores the multifaceted perspectives of participants in Science, Technology, Engineering, and Mathematics (STEM) fields, including educators, students, and technical staff, concerning the integration and implications of AI in higher education settings. To gather detailed insights into the lived experiences of these stakeholders, the research employs a qualitative methodology, utilizing in-depth interviews and focus group discussions. This approach allows for a rich collection of perspectives that reveal not only the enthusiasm surrounding AI’s potential to enhance learning outcomes and streamline administrative processes but also the apprehensions tied to its implementation. Participants express varied attitudes toward AI integration, with some embracing its ability to personalise learning experiences, enhance student engagement, and support educators in delivering more effective instruction. Conversely, concerns emerge regarding critical issues such as data privacy, the potential for exacerbating existing inequalities in access to technology, and the necessity of pedagogical adjustments to accommodate AI tools. The findings from this study underscore the complexity of AI’s role in higher education, illustrating the need for a thoughtful and strategic approach to its implementation. As institutions seek to harness the benefits of AI for improved educational outcomes, it becomes increasingly important to address the ethical considerations associated with its use. Recommendations from the study advocate for comprehensive faculty training to ensure educators are well-equipped to utilise AI effectively. Additionally, there is a call for revising curriculum development to incorporate AI technologies meaningfully, alongside fostering collaborative partnerships with industry to bridge the gap between theoretical knowledge and practical application.